Expression pattern of programmed death-1 in lymphocyte-rich classical Hodgkin lymphoma according to the growth patterns - Jai Hyang Go (Wolters Kluwer Medknow Publications, 2016)
We present a rare case of lymphocyte-rich classical Hodgkin lymphoma (LRCHL), which exhibited different expression patterns of programmed death-1 (PD-1) in nodular and interfollicular areas. A 57-year-old male patient presented with neck masses. Neck computed tomography showed enlargement of multiple lymph nodes in right Level II and III. Histologic examination of the excised lymph node revealed LRCHL with nodular and interfollicular patterns. Immunohistochemical analysis for PD-1 revealed a small number of weakly stained cells in the interfollicular area. PD-1 (+) cells were markedly increased in cell number and staining intensity in the nodular area and formed rosettes around the tumor cells.